Complexes of a piperazine based macrocycle as Cu-Zn SOD biomimetic: approach by constants determination - Armando Ferrer Serrano; Ilena Alica García Del Toro (The Journal of Engineering and Exact Sciences)
Obtaining new compounds capable of catalyzing the dismutation reaction of the superoxide anion carried out by the enzyme Cu,Zn-SOD has become a topic of great interest. In the present work, the study of a ligand with a piperazine fragment and its Cu(II) and Zn(II) complexes is introduced. The protonation constants of the ligand, the stability constants of the complex species un with equivalent of Cu(II) and Zn(II), forming both mononuclear and heterobinuclear species, in the presence and absence of histidine as secondary ligand were determined. For all cases, species distribution diagrams were obtained, from which the spectra in the visible region of the species of greatest interest were obtained. As an approach to the Cu,Zn-SOD system, the formation of quaternary species formed between these ions, the main ligand and histidine as a secondary ligand, was verified, which could be used as mimetics of said enzyme. Some theoretical studies were carried out to support this study.